Predicting minimum energy structure of a peptide via a modified potential smoothing kernel - Leong, Wah June; Abu Hassan, Malik (Institute for Mathematical Research, Universiti Putra Malaysia, 2008)
A global optimization approach is proposed for finding the global minimum energy configuration of a peptide. First, the original nonsmooth total potential energy function of a peptide, composed using the AMBER model, is transformed to a smoother function (shifted-impulsive transformation) via a procedure performed for each pair potential that constitute the total potential energy function. Then, the Potential Smoothing and Search (PSS) procedure is used to provide the global minimum. Based on this procedure global optimum solution is generated for a synthesis peptide named Compstatin.